Periklanan Politik Identitas : (Studi Pada Iklan Azan Ganjar Pranowo) (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam (IAI) Al-Aziziyah Samalanga, 2024)
Religious political communication must be conducted tactfully and responsibly. Politicians and religious leaders should seek to promote religious tolerance, harmony and diversity, while avoiding tension-fueled rhetoric. Political identity is a belief, value and attitude that gives a person a view of politics. Political advertising is an attempt to promote a particular candidate or political party. The research method used qualitatively with semiotic analysis, the media text analysis model used in this study is the Charles Sanders Peirce model. The purpose of the researcher to examine the identity politics advertisement of the ad show featuring Ganjar is to examine the food and purpose and identify whether the political identity in the call to prayer is present. The results of the research obtained the pros and cons of the azan ad shown on one of the private TVs that became a video talent are one of the presidential candidates in the 2024 election, namely Ganjar Pranowo. The result of the analysis of the controversy that occurred was that it was one of the groups of identity politics and some others argued that the question was a religious tolerance.